The Impact of the Kalamazoo Promise on School Climate - Gary Miron; Jeffrey N. Jones; Allison J. Kelaher-Young (Arizona State University, 2011)
The Kalamazoo Promise was announced in the fall of 2005, offering free college tuition at any public state college or university for graduates of the district who have gained acceptance to a postsecondary institution. This program was funded through the generous support of anonymous donors, and a federally-funded evaluation is underway to examine potential changes that result from its implementation. This paper situates perceptions of school climate in this moment of punctuated equilibrium of school reform, and in the context of this universal postsecondary scholarship program. This evaluation research draws from multiple data sources including interviews with educators, and surveys and interviews with students in the school district. Findings indicate that school climate has improved since the announcement of the program. We discuss the implications of research findings and the potential of the Kalamazoo Promise as a catalyst for systemic change in the district.